Construction of ultrafine ZnSe nanoparticles on/in amorphous carbon hollow nanospheres with high-power-density sodium storage. (May 2019) - Lu, Shiyao; Zhu, Tianxiang; Wu, Hu; Wang, Yuankun; Li, Jiao; Abdelkader, Amr; Xi, Kai; Wang, Wei; Li, Yanguang; Ding, Shujiang; Gao, Guoxin; Kumar, R. Vasant
Abstract: Sodium-ion batteries (SIBs) are considered as a promising candidate to lithium-ion batteries (LIBs) owing to the inexpensive and abundant sodium reserves. However, the application of anode materials for SIBs still confront rapid capacity fading and undesirable rate capability. Here we simultaneously grow ultrafine ZnSe nanoparticles on the inner walls and the outer surface of hollow carbon nanospheres (ZnSe@HCNs), giving a unique hierarchical hybrid nanostructure that can sustain a capacity of 361.9 mAh g −1 at 1 A g −1 over 1000 cycles and 266.5 mAh g −1 at 20 A g −1 . Our investigations indicate that the sodium storage mechanism of ZnSe@HCNs electrodes is a mixture of alloying and conversion reactions, where ZnSe converts to Na2 Se and NaZn13 through a series of intermediate compounds. Also, a full cell is constructed from our designed ZnSe@HCNs anode and Na3 V2 (PO4 )3 cathode. It delivers a reversible discharge capacity of about 313.1 mAh g −1 after 100 cycles at 0.5 A g −1 with high Columbic efficiency over 98.2%. The outstanding sodium storage of as-prepared ZnSe@HCNs is attributed to the confinement of ZnSe structural changes both inside/outside of hollow nanospheres during the sodiation/desodiation processes. Our work offers a promising design to enable high-power-density electrodes for the various battery systems. Graphical abstract: A hierarchical hybrid nanocomposite of ultrafine ZnSe nanoparticles growing on/in amorphous hollow carbon nanospheres (ZnSe@HCNs) has been prepared via simple solution reflux and post-calcination in Ar/H2. The ZnSe nanoparticles grow on both sides of HCNs, thus preventing severe aggregation and stabilizing structures of electrodes upon cycling. When used as a promising anode for SIBs, the hybrid composites could manifest excellent electrochemical performance with high reversible capacity, long-term cyclic stability and excellent rate capability.Image 1 Highlights: ZnSe nanoparticles grow on both the inner walls and the outer surface of hollow carbon nanospheres (ZnSe@HCNs). The sodium storage mechanism of ZnSe@HCNs electrodes is a mixture of alloying and conversion reactions. A full cell constructed from the ZnSe@HCNs anode and Na3 V2 (PO4 )3 cathode was demonstrated. ZnSe@HCNs exhibit long-cycle and high-rate sodium storage. The robust structure can accommodate the large volume and structural changes.